A course on damage mechanics - Lemaître, J. (Jean), 1934- (Springer, 1996)
This well-established textbook teaches macroscopic modeling for design, processing, testing, and control of mechanical components in engineering. The first chapter deals with the phenomenology of damage; the second couples damage to strains and covers the three-dimensional situation; the third is devoted to kinetic laws of damage evolution used by the author to unify many models; the fourth gives several methods for predicting crack initiation. Detailed calculations and many exercises help students to apply the powerful techniques to practical problems in engineering. This second, corrected and enlarged edition also includes the damage of interfaces and statistical damage analysis with microdefects.